Cyberbullying In the Perspective of Islamic Criminal Law - Mukhlis Akbar Ramadhani; Adinda Putri Hutabarat; Alwi Almisky Munthe; Ending Solehudin (ISNU Sumatera Utara, 2024)
The rapid development of information and communication technology has significantly transformed patterns of social interaction while simultaneously giving rise to new forms of crime, including cyberbullying. Cyberbullying has become a serious legal issue due to its detrimental effects on victims' psychological well-being, personal dignity, and reputation. Although Indonesia has enacted Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 on Electronic Information and Electronic Transactions (ITE Law), the regulation does not explicitly define cyberbullying as a distinct criminal offense but addresses related acts such as defamation, threats, extortion, and intimidation committed through electronic media. This study aims to analyze the legal regulation of cyberbullying under the ITE Law and examine its legal consequences from the perspective of Islamic criminal law. This research employs a normative juridical method with a descriptive-analytical approach based on statutory, conceptual, and literature studies. The findings indicate that cyberbullying constitutes a form of cybercrime involving electronic media to threaten, intimidate, humiliate, or damage another person's reputation. Under Indonesian positive law, perpetrators may be prosecuted under several provisions of the ITE Law and the Criminal Code depending on the nature of the offense. From the perspective of Islamic criminal law, cyberbullying is categorized as a ta'zir offense because no specific punishment is prescribed in the Qur'an or Hadith. Consequently, the determination of sanctions is left to the discretion of the legitimate authority (ulil amri) to ensure justice, public order, and the protection of individual honor. The study concludes that both Indonesian positive law and Islamic criminal law share the same objective of protecting human dignity and preventing harm caused by cyberbullying, despite adopting different legal approaches to determining criminal sanctions.